Is small 'beautiful' for economic integration : the Americas. - GUTIERREZ, Mario A. (1996)
Reviews the potential limitations and characteristics of small economics, and focuses on some implications of trade openness and trade dependence for macro-economic management and integration. Examines the issue of disparities and its relevance for trade and economic integration of small countries. Summarises the main observations and implications for the integration of small economies in North and South America into the Free Trade Area of the Americas (FTAA).